How to best distribute written patient education materials among patients with rheumatoid arthritis: a randomized comparison of two strategies - Aniek A. O. M. Claassen; Cornelia H. M. van den Ende; Jorit J. L. Meesters; Sanne Pellegrom; Brigitte M. Kaarls-Ohms; Jacoba Vooijs; Gerardine E. M. P. Willemsen-de Mey; Thea P. M. Vliet Vlieland (BMC, 2018)
Abstract Background The aim of this randomized controlled trial was to evaluate the effect of a 'supply on demand'-distribution strategy, compared to an 'unsolicited supply'-distribution strategy, on the use of a care booklet and clinical outcomes among patients with rheumatoid arthritis (RA). In addition, differences in socio-demographic and clinical characteristics between users and non-users were explored. Methods As part of regular care the care booklet was distributed among RA-patients of two hospitals in the Netherlands. 1000 patients received the care booklet by mail, whereas another 1000 received an information letter with the option to order the care booklet. Four months after distribution, a random sample of 810 patients (stratified by hospital and distribution method) received a questionnaire on the use of the booklet, social-demographic and clinical characteristics. To compare effects between the two distribution strategies and differences between users and non-users univariate and multilevel regression analyses were performed. Secondary analysis included a per-protocol analysis (excluding participants who did not order the care booklet). Results One hundred ninety four patients in the 'unsolicited supply' and 176 patients in the 'supply on demand' group (46%) returned the questionnaire. In the 'supply on demand' group 106 (60.2%) participants ordered the care booklet. In total, no difference was found in use between the 'unsolicited supply'-group (23.2%) and the 'supply on demand'-group (21.6%) (OR 0.9 CI:0.6-1.5). However, the proportion of users among patients in the 'supply on demand'-group who ordered the booklet (35%) was significantly higher than in the 'unsolicited supply'-group (OR 1.9 CI:1.1-3.2). Regardless of distribution method, use of the care booklet was associated with being married (OR 2.4 CI:1.2-4.6), higher disease activity (mean difference 0.5 CI: 0.0-1.1), more activity limitations (mean difference 0.2 CI: 0.1-0.4), use of corticosteroids (OR 1.9 CI:1.0-3.5), perception of disease course as fluctuating (mean difference 1.4 CI:0.5-2.3) and higher educational needs (mean difference 9.7 CI: 2.9-16.6). Conclusions From an economic and environmental perspective a 'supply on demand'-distribution strategy could be recommended. Results of this study provide starting points to optimize further implementation strategies of a care-booklet in routine care. Trial registration ISRCTN registry (ISRCTN22703067). Retrospectively registered 27 March 2017.